2001
DOI: 10.1097/00006534-200109150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Video Microsurgery: Evaluation of Standard Laparoscopic Equipment for the Practice of Microsurgery

Abstract: Traditional microsurgery involves the use of bulky and expensive stereo microscopes that have limited portability. Recent advances in video technology have enabled the exploration of alternative visualization methods. The purpose of this study was to evaluate standard laparoscopic equipment for microvascular anastomoses. Eight surgeons completed anastomoses on rat femoral and synthetic vessels using stereo microsurgery and video microsurgery visualization systems. All surgeons had previous experience with ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…This amount should be added to the operative time in the research operative room, cost of anesthetics and microsurgical supplies. The utilization of the exceeding population of rats, common at research facilities of great ongoing research from times to times, may give the provider some relief to reduce costs substantially 1,11,12 .…”
Section: Inmentioning
confidence: 99%
“…This amount should be added to the operative time in the research operative room, cost of anesthetics and microsurgical supplies. The utilization of the exceeding population of rats, common at research facilities of great ongoing research from times to times, may give the provider some relief to reduce costs substantially 1,11,12 .…”
Section: Inmentioning
confidence: 99%
“…The system is massive and fixed around the wound, being difficult to handle even for the foot pedal controlled microscope. 5 The surgeon's position is sometimes uncomfortable, because of the anatomic area where he/she wishes to work and even more so for the assisting personnel.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The greatest advantage is that it can be built using the components of a laparoscopic surgery support tower, which is used in various surgical fields. The overall costs for the health-care unit are therefore substantially reduced and can be paid off in the shortest time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous failures of endoscopic microvascular surgery may have also deterred plastic hand and soft tissue reconstructive surgeons from attempting robotic surgery [7,8]. Study has shown transfer of skills in experienced microsurgeons is limited when compared to relative novices [9].…”
Section: Microvascular and Microneural Surgerymentioning
confidence: 99%